PENDAMPINGAN PENINGKATAN FUNGSI KOGNITIF dan PENURUNAN LONELINESS MELALUI MOVEMENT THERAPY pada PASIEN SKIZOFRENIA dengan ISOLASI SOSIAL di UPT RSBL PASURUAN - Widowati, Sri; Muhammad Rosyidul 'Ibad; Muhammad Ari Arifianto (P3M Universitas Aisyiyah Surakarta, 2024)
Schizophrenia interferes with many aspects of a patient's life, causing deficits in cognitive, perceptual, motor, emotional, and social functioning. Patients who experience social isolation can feel loneliness, with decreased interaction that will also affect their cognitive function. There were 183 schizophrenia patients in the social rehabilitation unit, and around 25% (45) patients with symptoms of social isolation. This condition causes the patient to experience a decrease in activity which in the end the patient becomes unproductive, the patient's quality of life decreases and the prognosis for schizophrenia will get worse. This condition will increase the burden of care for both the family and the patient's place of care, and if the burden of caring increases, the quality of caring will decrease. One of the psychotherapy recommendations for schizophrenia patients with social isolation is movement therapy. Movement therapy used in this activity is dance movement therapy and aerobic therapy. The patients involved in this activity were 10 patients for dance movement therapy and 10 patients for aerobic therapy. The results obtained after the implementation of dance movement therapy were that the patient experienced a decrease in the loneliness scale in 10 patients. Meanwhile, aerobic therapy for ten patients experienced an increase in cognitive function of 1-3 scores. This method can be developed in the form of audio-visual and the patient can do it alone without being accompanied by a therapist and being observed. So that this activity can be a recommendation for additional therapy in schizophrenia patients with social isolation. Key words : Movement therapy, dance movement therapy, aerobic therapy, social isolation